COMPETITION STRATEGY ANALYSIS WITH A SWOT ANALYSIS APPROACH TO INCREASE PROFIT OF MSME KNOWLEDGE SELLERS IN KETAJEN VILLAGE, SIDOARJO (Ekspektra : Jurnal Bisnis dan Manajemen, 2022)
In a business, never escape from competition. Whether it's a large, medium, or even small business, there will definitely be competitors. This is what makes researchers determined to analyze the form of competition and the strategies used to deal with it. Especially in the morning the MSME street vendors who lack knowledge about competition and the analyzes they can use to win the competition. The purpose of the researchers conducting this research is to find out and analyze the impact of competitive advantage on increasing the profits of the MSME street vendors selling "Tahu Tek". The method used is descriptive qualitative research with inferential statistical analysis by comparing MSMEs with one another and adapting them to the theories of experts. The results of this study indicate that competitive advantage by implementing a competitive strategy can increase the profits of SMEs selling "Tahu Tek". Based on the suitability of the theory of competitive strategy with increased profit is related. As well as between MSMEs that apply a competitive strategy and MSMEs that do not apply a competitive strategy, there is a significant difference.